The psychological impact of torture - de C Williams, Amanda C (Br J Pain, 2013)
Many refugees in the developed world are survivors of torture and present with health needs without their traumatic experience being disclosed or identified. Chronic pain is a common problem, as are symptoms of post-traumatic stress disorder (PTSD), anxiety, depression, and other distress. Current circumstances, particularly poverty, uncertainty about asylum, separation from or loss of family and roles, and difficulties settling in the host country, all contribute to current psychological problems and exacerbate existing ones. Psychological treatment studies tend to be focused either on PTSD diagnosis and use protocol-driven treatment, usually in the developed world, or on multiple problems using multimodal treatment including advocacy and welfare interventions, usually in the developing world. Reviews of both of these, and some of the major criticisms, are described. Psychological interventions tend to produce medium-sized changes in targeted measures of distress, when compared with waiting lists or standard treatment, but these may fall well short of enabling recovery, and long-term follow-up is rare. A human rights context, with reference to cultural difference in expressing distress and seeking help, and with reference to the personal meaning of torture, is essential as a basis for formulating treatment initiatives based on the evidence reviewed. SUMMARY POINTS: Refugees with a history of torture may have a wide range of psychological and social difficulties which do not easily fit within diagnostic categories. Torture and its sequelae can have multiple meanings and, in the clinical context, it is the interpretation of the torture survivor that matters. There are doubts about applying the concept and measures of post-traumatic stress disorder: symptoms should be assessed separately. Current circumstances can be as important as trauma history in understanding the psychological state of a torture survivor. Cognitive behavioural therapy and narrative exposure therapy seem equally effective in reducing trauma symptoms, and to a lesser extent, depression.